Catalogue of scalable innovative packages to inform climate action investments in Africa: Case studies from Kenya, Zambia and Ethiopia - Chepcheng, Lynn; Mulama, Leon; Kung'u, Fredrick; Kimanzi, Meshack; Adhiambo, Petronilla; Denje, Telvin; Wamukoya, George; Chilambe, Pedro (2025)
This Climate Innovations Catalogue consolidates innovative, replicable, and scalable climate interventions implemented across Kenya, Ethiopia, and Zambia, sourced from the CGIAR Results Dashboard. It serves as a one-stop reference for development partners, government agencies, investors, and practitioners seeking to design and implement bankable climate adaptation projects. The catalogue compiles project-based innovations with demonstrated results, highlights key implementation partners, and outlines the technical and financial considerations necessary for scaling. Its primary objective is to support stakeholders in identifying investment-ready climate solutions that enhance resilience, foster collaboration, and promote sustainable development outcomes across diverse contexts in Eastern and Southern Africa